Carotenoid Supplementation in Poultry Nutrition: Canthaxanthin’s Role in Improving Egg Yolk Pigmentation and Production Efficiency - Atmaja, Baluh Medyabrata; Hidayatulloh, Rifqi; Ali, Muhammad Irvan; Hutabarat, Amelia Lulu Rosalin; Safitri, Alief Rahmania; Ali, Abdul Muta; Lestari, Wenni Meika (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2025)
Egg yolk pigmentation is a crucial quality attribute influencing consumer preference and market value. This study evaluated the effects of Canthaxanthin supplementation on yolk pigmentation and laying performance in late-stage laying hens (84–88 weeks old). A total of 180 Isa Brown hens were assigned to three dietary treatments: a control group (T0: commercial feed), a low Canthaxanthin supplementation group (T1: commercial feed + 60 g/ton feed Canthaxanthin), and a high supplementation group (T2: commercial feed + 120 g/ton feed Canthaxanthin). The data were analyzed using SPSS software (version 25.00), and a one-way analysis of variance (ANOVA) was performed to assess the effects of Canthaxanthin supplementation on laying performance and egg quality, with significance set at p<0.05. Duncan’s multiple range test was used post hoc to identify significant differences between treatment groups. Egg production performance, egg mass, feed conversion ratio, and yolk quality were assessed over a five-week period. Results indicated that Canthaxanthin supplementation significantly improved yolk color, with the highest color score recorded in T2. While egg production and feed efficiency remained unaffected, egg mass increased significantly in the supplemented groups (p<0.05), suggesting improved nutrient deposition. Additionally, feed intake was slightly higher in the high supplementation group. These findings confirm that Canthaxanthin is an effective dietary additive for enhancing yolk pigmentation while maintaining production efficiency in aging hens. The study highlights the potential economic benefits of Canthaxanthin supplementation in meeting consumer demand for well-pigmented eggs. Future research should explore its long-term effects on oxidative stability, egg lipid composition, and potential synergies with other dietary antioxidants to optimize poultry nutrition strategies.